PERANCANGAN SISTEM PELAYANAN MAHASISWA PADA STMIK KHARISMA MAKASSAR DENGAN MENGGUNAKAN FRAMEWORK CODEIGNITER - Royan Haris Widodo; Syaiful Rahman; Hamdan Arfandy (JTRISTE, 2018)
This research aim to build a College Student Service Computerisation system by using a Framework Codeigniter at STMIK Kharisma Makassar. Framework codegniter used as college student service system web-based because framework codeigniter using a MVC (Model View Controller) which build a web programme become more structured and framework codeigniter can also work with PHP 5. Data collecting method to collect requirement specification and system development are done by an interview activity and study literature. For Data Model using an ERD (Entity Relationship Diagram). Application testing result which developed shows that score demand service and document demand service will be easier because we can do it online. Meanwhile BAAK administration and prodi can further the demand service process. This testing shows that Application which being developed is used as a communication media between two sides in a score demand process service and documents demand service online.